Product Marketing Strategy in the Store Mulia Baruga Bantaeng Regency - Rusly, Selmiaty; Seppa, Yusi Irensi; Syarifuddin, Syarifuddin; Siraj, Muh Luthfi (Jurnal Administrasi Bisnis, 2026)
This study aims to determine the marketing strategy carried out at Toko mulia baruga Bantaeng Regency by explaining the marketing mix to increase sales turnover. The type of research used is qualitative descriptive, which is an analysis used to describe or solve problems systematically with the SWOT analysis method. To achieve the objectives of the study, data collection techniques were used, namely observation / observation, interviews and documentation with 7 information people from store owners, employees, and consumers. The validity of the data is checked using the source triangulation technique. Data analysis techniques use data collection, data condensation, data presentation and conclusions. The results showed that the strategy that can be applied by noble Baruga shop owners is a diversification strategy. By carrying out a diversification strategy, Toko mulia baruga can develop and improve products, distribution processes, prices and promotions for consumers. The supporting factors of Toko mulia baruga are that the goods sold are quite varied in their strategy, have good quality goods, store locations that are easily accessible, for customers outside the area can make direct purchases easily. While the inhibiting factors of Toko mulia baruga are not yet having branches, promotions that are not optimal, the problem of price differences that can only slightly reduce customers.Keywords: Strategy, marketing, SWOT Analysis